Promoting accountability under international law for gross human rights violations in Africa : essays in honour of prosecutor Hassan Bubacar Jallow - Jalloh, Charles; Marong, Alhagi B. M.; Jallow, Hassan B. (Brill Nijhoff, 2015)
Promoting Accountability under International Law for Gross Human Rights Violations in Africa is pre-eminently a study on the work and contribution of the first international judicial mechanism, the International Criminal Tribunal for Rwanda (ICTR), devoted exclusively to challenging impunity for serious international crimes committed in Africa. This volume is dedicated to the eminent international jurist Justice Hassan Bubacar Jallow, the Tribunal's longest serving Chief Prosecutor and the first prosecutor of the United Nations Mechanism for International Criminal Tribunals. The noted scholar and practitioner contributors discuss various aspects of the law, jurisprudence and practice of the Tribunal over its twenty year existence, while also drawing lessons for current and future international courts such as the International Criminal Court. Themes covered include the role of the international prosecutor; the prosecution of sexual and gender-based crimes; the relationship between national and international courts; the role of other international institutions in challenging impunity; and the role of African languages in international criminal trials. Given its wide ranging substantive coverage, this book will be invaluable to anyone interested in criminal justice, human rights and humanitarian law whether in Africa or other parts of the world.